The clinical impact of prolonged steroid therapy in severe COVID-19 patients: a retrospective cohort study with propensity score matching - Jaijun Han; Seongman Bae; Jiwon Jung; Min Jae Kim; Yong Pil Chong; Sang-Ho Choi; Sang-Oh Lee; Yang Soo Kim; Euijin Chang; Sung-Han Kim (BMC Pulmonary Medicine)
Abstract Background The optimal duration of steroid therapy for patients with COVID-19 remains unclear. This study compared clinical outcomes between early steroid withdrawal (EW; ≤10 days) and prolonged steroid tapering (PT; >10 days) in patients with severe COVID-19 requiring oxygen support. Methods This retrospective, single-center cohort study included adult patients with COVID-19 and WHO-CPS scores of 6–9 admitted to a tertiary hospital in Seoul, Republic of Korea. After 1:1 propensity score matching, 68 patients were included in each group. Primary outcomes were 28-day and 60-day mortality. Secondary outcomes included clinical aggravation, rebound pneumonia, infectious complications, readmission or emergency department (ED) revisits, duration of oxygen support, and lengths of hospitalization and ICU stay. Results Baseline characteristics were well balanced after matching. No significant differences were observed in 28-day mortality (5.9% vs. 10.3%, HR 0.54, 95% CI 0.16–1.84, p = 0.32) or 60-day mortality (14.7% vs. 11.8%, HR 1.22, 95% CI 0.48–3.10, p = 0.67) between PT and EW groups. Rates of clinical aggravation, rebound pneumonia, infectious complications, and readmission or ED revisit were also comparable. However, the PT group had significantly longer durations of oxygen support (17.5 vs. 13.0 days, p = 0.001), hospitalization (20.0 vs. 14.0 days, p = 0.001), and ICU stay (5.0 vs. 1.0 days, p = 0.01). Conclusions Prolonged steroid therapy beyond 10 days did not improve survival or other clinical outcomes in patients with severe COVID-19, suggesting that early steroid withdrawal may be appropriate for selected patients.